The Crystallization, Melting Behavior, and Thermal Stability of Poly(L-lactic acid) Induced by N,N,N′-Tris(benzoyl) Trimesic Acid Hydrazide as an Organic Nucleating Agent - Yan-Hua Cai; Yan-Hua Zhang (Advances in Materials Science and Engineering)
N,N,N′-Tris(benzoyl) trimesic acid hydrazide (TTAD), as a novel nucleating agent of poly(L-lactic acid) (PLLA), was synthesized and characterized by FT-IR and 1H NMR. The crystallization, melting behavior, and thermal stability of PLLA induced by TTAD were investigated through DSC, TGA, depolarized-light intensity measurement, and so forth. The crystallization behavior indicated that the presence of TTAD accelerated the overall PLLA crystallization. Compared to neat PLLA, the crystallization onset temperature of PLLA/1%TTAD increased from 101.36°C to 125.26°C, the melt-crystallization peak temperature increased from 94.49°C to 117.56°C, crystallization enthalpy increased from 0.1023 J·g−1 to 33.44 J·g−1 at a cooling rate of 1°C/min from melt, and the crystallization half-time of PLLA/TTAD decreased from 2997.2 s to 108.9 s at 110°C. Moreover, the nonisothermal crystallization measurements also indicated that the crystallization peak became wider and shifted to a lower temperature with increasing cooling rate. With the presence of TTAD, the melting behavior of PLLA was affected significantly, and a double-melting peak occurred due to melting-recrystallization. Thermal stability research showed that there existed one degradation stage of PLLA and PLLA/TTAD samples, and the thermal degradation temperature of PLLA/TTAD decreased compared to neat PLLA.